Pendampingan Perencanaan Area Parkir Pada Objek Wisata Pulau Semut Kelurahan Limbungan Kota Pekanbaru - Anggraini, Muthia; Trisep Haris, Virgo; Masrul, Wati (Jurnal Pengabdian KOLABORATIF, 2026)
Pulau Semut is a tourist destination managed by a community-based tourism awareness group. The group collaborates to develop and improve the tourism site in order to ensure visitor safety and comfort. As Pulau Semut has become increasingly popular and attracts more visitors, the availability of adequate parking facilities has become an important issue. Currently, parking areas utilize vacant land without proper planning, and visitors tend to park near their activity locations. Therefore, every tourism destination needs to provide well-organized and sufficient parking facilities. Due to limited resources in parking area planning, the community partner required technical assistance to optimize the available land for parking purposes. The implementation method included field surveys, identification of existing conditions, and focused discussions. The result of this activity was a parking area plan located beside the entrance ticket post, using paving block materials while preserving existing trees within the parking area. This activity supports the improvement of tourism supporting infrastructure, and the addition of a designated parking area is expected to enhance visitor comfort and overall tourism service quality.